2017
DOI: 10.1177/1558944717692086
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Common Hand Injections With and Without Ultrasound: An Anatomical Study

Abstract: Carpal tunnel, first DC, and RC injections had an accuracy of greater than 90%. Thumb CMC injections have a lower accuracy (63%) and one can improve accuracy with U/S. The accuracy of U/S-guided injections is dependent on the user and their experience.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 17 publications
0
23
0
Order By: Relevance
“…There is controversy in the literature regarding the increased accuracy of ultrasound-guided injections (USIs) as compared to landmarkbased-guided injections. One study showed that use of US increased the accuracy of carpometacarpal (CMC) joint injection from 63 to 94%, but did not significantly improve injection accuracy of other hand joints [5]. This review will additionally outline the effects of compounds injected for each hand condition, such as corticosteroids, hyaluronic acid (HA), and botulinum neurotoxin.…”
Section: Introductionmentioning
confidence: 99%
“…There is controversy in the literature regarding the increased accuracy of ultrasound-guided injections (USIs) as compared to landmarkbased-guided injections. One study showed that use of US increased the accuracy of carpometacarpal (CMC) joint injection from 63 to 94%, but did not significantly improve injection accuracy of other hand joints [5]. This review will additionally outline the effects of compounds injected for each hand condition, such as corticosteroids, hyaluronic acid (HA), and botulinum neurotoxin.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, particularly debated was the accuracy of TBOA injections with and without imaging guidance, nowadays represented essentially by ultrasound. Indeed, the consensus statement on viscosupplementation ( Henrotin et al, 2015 ) suggested to inject the trapezio-metacarpal joint under fluoroscopy or ultrasonography guidance and a recent United States cadaveric study showed a 25% higher accuracy when thumb-base joint was injected with ultrasound guidance compared to no imaging control ( To et al, 2017 ). Conversely, other studies demonstrated success rates comparable with those obtained under ultrasound-control when the injections were performed by an experienced physician based on palpation of landmarks ( Helm et al, 2003 ; Mandl et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%
“…Fluoroscopy demonstrated a 42% inaccuracy rate. 5 To et al 18 reviewed the accuracy of ultrasound-guided injections of several hand sites and found that CMC joint accuracy was improved by 25% with ultrasound. Hunter et al 9 also demonstrated poor accuracy of thumb CMC joint injections (63.6%) using anatomic landmarks compared with fluoroscopy-guided injection.…”
Section: Discussionmentioning
confidence: 99%